Avaliação da atividade da invertase de Saccharomyces cerevisiae imobilizada em polianilina sobre o caldo de cana - BARBOSA, Eduardo Fernandes (2010)
This work describes the immobilization of invertase on chemically synthesized polyaniline and activated with glutaraldehyde (PANIG) for production of invert syrup from sugarcane juice. Free invertase activity present in crude extract (E.B.) obtained from cells of Saccharomyces cerevisiae, was characterized for an evaluation of interferents present in the extract on enzyme activity (optimum conditions: temperature 50 ° C, pH of 4.5 in sodium acetate buffer 0.1 mol L-1 and reaction time of 10 minutes, with an activity of 11.31 ± 0.36 EU mL-1). We tested some parameters optimization of enzyme immobilization, such as amount of enzyme, immobilization time, pH and temperature of immobilization. The optimal immobilization was obtained in buffer sodium acetate 0.1 mol L-1 pH 4.5, immobilization time of 1 hour at 50°C and 169.55 EU mg-1 PANIG. The efficiency of immobilization was 0.86. The stability of the system PANIG-Invertase was tested against the storage time and thermostability, and after 75 days storage in buffer sodium acetate 0.1 mol L-1 pH 4.5 was obtained for 94% of initial activity with only 17% retained for the free enzyme. The immobilized invertase didn t change the optimal conditions compared to the free, but the immobilized was more stable in adverse conditions such as pH below and above optimum conditions showed an increase in thermostability. Some features of the hydrolysis product were evaluated (water activity, viscosity and color), compared to the sugarcane juice in nature, showing that the reactors allowed changes in sugarcane juice that expand the possibilities for using syrup obtained in the production of sweets, ice cream and syrups rich in fructose. The high stability of the system tested, along with its high retention of activity strongly suggests the use of the system in reactors.